(untitled) (Journal of Academic Research, 2020)
This study aims to explain the reality of Zakat Accounting on trade offers in Libya, the study employed structure interviews as the main tool to collect the intended data from staffs of Misurata Zakat Fund Office. The significance of this study lies in the fact that it focuses on the Zakat of trade offers, in general and Misurata Zakat Fund Office in particular, while most previous studies focus on Zakat in general, few studies focus on the local environment in Libya. Descriptive approach which is based on studying the phenomenon as it exists used in this study in order to achieve its objectives. The study findings revealed that the lack of coordination and cooperation between the Zakat Fund and the Tax Authority led to the delay in paying Zakat. Also due to the liquidity crisis in banks most of the Zakat funds are in the form of Checkbook which in somehow make the process of withdraw a difficult from the banks and deliver the zakat the beneficiaries.